Assessing Egyptians' knowledge, perceptions, and attitudes towards generic medicines - Elmoneer, Radwa Ahmed (AUC Knowledge Fountain, 2019)
Medicines are vital component of any health system worldwide, and ensuring accessibility of affordable, effective and safe medications is a critical public policy goal considered by every country. Egypt has, recently, faced aggravated challenges in ensuring the availability of medications countrywide. In response, the Egyptian government has adopted a number of pharmaceutical policies and interventions, mainly, targeting the supply side of the market. Promoting the use of generic medicines is an effective policy intervention that addresses the demand side, a highly recommended intervention given other countries’ experiences. As the main users of medications, patients are a crucial source of knowledge for decision and policymakers. Therefore, prior to implementing any policy intervention to promote the use of generic medicines, it is vital to assess their knowledge and understand their perspectives towards generic medicines, as a quality-insured, cost-effective, and therapeutically equivalent alternative.